Absorption of scalar waves by static black holes and analogues - Crispino, Luís C.B.; Oliveira, Ednilton S.; Dolan, Samuel R.; Matsas, George E.A. [UNESP] (World Scientific Publishing, 2012)
We compute numerically the scalar absorption cross section for Reissner-Nordstrom black holes and the absorption cross section of canonical acoustic holes. Copyright © 2012 by World Scientific Publishing Co. Pte. Ltd.
Keywords: Absorption cross section; Analogues; Scalar field; Static black holes